2016
DOI: 10.1159/000443848
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hemodialysis Patient Outcomes and Compliance with KDOQI and KDIGO Targets for Mineral and Bone Metabolism

Abstract: Background: Increased mortality of hemodialysis (HD) patients is associated with chronic kidney disease-mineral and bone disorders (CKD-MBD), and therefore, their correction may improve patient survival. Differences in targets recommended by KDOQI and KDIGO CKD-MBD guidelines directed us to compare the relative numbers of patients achieving these targets and to examine possible associations between compliance with the targets and patient outcome. Methods: A total of 1,744 patients (61.2% males, aged 58.7 ± 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…In spite of dietary restrictions and widespread phosphate binder use, a significant number of patients are not able to reach the target phosphate serum level. 5 There are multiple factors involved: non-compliance to the dietary restrictions and phosphate binder use, 6 bone derived phosphate and pharmacological aspects of phosphate binders. Furthermore, less acidic environment in use of proton pump inhibitors can be of influence, since lanthanum carbonate and calcium carbonate bind more phosphate in acidic surroundings.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of dietary restrictions and widespread phosphate binder use, a significant number of patients are not able to reach the target phosphate serum level. 5 There are multiple factors involved: non-compliance to the dietary restrictions and phosphate binder use, 6 bone derived phosphate and pharmacological aspects of phosphate binders. Furthermore, less acidic environment in use of proton pump inhibitors can be of influence, since lanthanum carbonate and calcium carbonate bind more phosphate in acidic surroundings.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Phosphate binders bind phosphate in the gastrointestinal (GI) tract resulting in less phosphate absorption. In spite of dietary restrictions and widespread phosphate binder use, a significant number of patients are not able to reach the target phosphate serum level . There are multiple factors involved: non‐compliance to the dietary restrictions and phosphate binder use, bone derived phosphate and pharmacological aspects of phosphate binders.…”
mentioning
confidence: 99%
“…These data suggest a causal link between hyperphosphatemia and increased mortality. The improvements in survival observed when serum abnormalities were close to the lowest risk ranges support the rationale for controlling this parameter in patients with advanced CKD [ 35 , 36 ]. However, whether this approach improves other clinical outcomes remains unproven.…”
Section: Epidemiology and Impact Of Hyperphosphatemia In Chronic Kidnmentioning
confidence: 97%
“…Many observational studies subsequently confirmed this association between hyperphosphatemia and increased risk of mortality, but by their design all these studies precluded definite establishment of causality [ 29 33 ]. While no randomized controlled trials to date have demonstrated that reducing serum phosphate concentrations reduces mortality [ 34 ], a 3-year study of 1744 patients receiving dialysis identified that having serum phosphate levels above the normal range was associated with a significantly higher risk of death [ 35 ]. Additional support for the presumed causal role of hyperphosphatemia in poor outcomes comes from COSMOS (Current Management of Secondary Hyperparathyroidism: a Multicenter Observational Study), a 3-year, European, multicenter, open-cohort, observational study designed specifically to prospectively assess possible links between serum phosphate, calcium, PTH levels, and mortality risk in adults undergoing maintenance hemodialysis ( n = 6307) [ 36 ].…”
Section: Epidemiology and Impact Of Hyperphosphatemia In Chronic Kidnmentioning
confidence: 99%
“…Predictors of a worse prognosis at the start of RRT include malnutrition and low albumin levels (Chan et al ; Takahashi et al ), frailty and comorbidity (Bao et al ; Pan et al ), age (Pan et al ), haemoglobin levels (Cherukuri & Bhandari ) and mineral metabolism disorders (Melamed et al ; Nigwekar et al ; Djukanović et al ).…”
Section: Literature Reviewmentioning
confidence: 99%